2015
DOI: 10.1186/s13058-015-0542-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of endocrine resistance in breast cancer: an overview of the proposed roles of noncoding RNA

Abstract: Endocrine therapies such as tamoxifen and aromatase inhibitors are the standard treatment options for estrogen receptor-positive breast cancer patients. However, resistance to these agents has become a major clinical obstacle. Potential mechanisms of resistance to endocrine therapies have been identified, often involving enhanced growth factor signaling and changes in the expression or action of the estrogen receptor, but few studies have addressed the role of noncoding RNA (ncRNA). Two important types of ncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 109 publications
2
114
0
1
Order By: Relevance
“…We therefore explored the molecular components that could be responsible for the metabolic and motile reprogramming that MCF7 cells undergo under LTED conditions and after 2-DG treatment. Deregulation of miRNA expression has been demonstrated in many types of cancer and the involvement of miRNAs has been previously described in breast cancer etiology (42) and in endocrine therapy response and resistance (43). For example, miR-221/222 was able to confer tamoxifen resistance (44), while reexpression of miR-375 (45), let-7 (46), miR-342 (47), or miR-320 (48) induced tamoxifen sensitivity.…”
Section: Discussionmentioning
confidence: 90%
“…We therefore explored the molecular components that could be responsible for the metabolic and motile reprogramming that MCF7 cells undergo under LTED conditions and after 2-DG treatment. Deregulation of miRNA expression has been demonstrated in many types of cancer and the involvement of miRNAs has been previously described in breast cancer etiology (42) and in endocrine therapy response and resistance (43). For example, miR-221/222 was able to confer tamoxifen resistance (44), while reexpression of miR-375 (45), let-7 (46), miR-342 (47), or miR-320 (48) induced tamoxifen sensitivity.…”
Section: Discussionmentioning
confidence: 90%
“…miRNAs are also associated with resistance to aromatase inhibitors. 60 Masri et al 61 suggested that miR-128a modulates the transforming growth factor-β signaling and survival of letrozole-resistant cell lines. miRNAs expression profiling before and after letrozole treatment reveal post-treatment increases in let-7f expression in both the preclinical and clinical settings.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…However, the fundamental clinical challenge associated with this treatment option is the development of resistance to endocrine therapy [2].The mechanisms of resistance have yet to be fully elucidated [2]. Among women with disease progression after prior endocrine therapy, treatment options include sequential endocrinebased therapies, as monotherapy or in combination with a targeted therapy (e.g., everolimus for some postmenopausal women), before switching to chemotherapy [1].…”
Section: Introductionmentioning
confidence: 99%